Leadership power perception of amateur and professional soccer coaches and players according to their belief in good luck or not - Konter, E. (Collegium Antropologicum, 2010)
The purpose of this study was to analyze the leadership power perception of amateur and professional soccer coaches and players according to their belief in good luck or not. Data collected from 165 male soccer coaches and 870 male soccer players including professionals and amateurs. The coaches had a mean age of 40.24 years (SD=8.40) and had been coaching for an average of 8.56 years (SD=6.75). The players had a mean age of 18.40 years (SD=4.00) and had been playing soccer for an average of 6.00 years (SD=4.15) with license. Adapted Turkish version of Power in Soccer Questionnaire- Other (PSQ-O for soccer players), Power in Soccer Questionnaire-Self (PSQ-S for coaches) and an information form were used for the data collection. Cronbach Reliability Alphas of PSQ-O and PSQ-S range between 0.60 and 0.84. Players` and coaches` data were analyzed by Kruskal-Wallis and Mann Whitney Tests. Analysis of PSQ-O revealed significant differences related to Coersive Power-CP [c2 (3) = 8.46, p<0.037], Referent Power-RP [c2 (3) = 14.84, p<0.002] and Expert Power-EP [c2 (3) = 7.63, p<0.054], and no significant differences related to Legitimate Power-LP (p>0.05). Results of PSQ-O and PSQ-S indicated complex relationships related to belief in good luck or not. Overall, there are differences between coaches` and players` perception of CP, LP and EP related to belief in good luck or not. The only similarity appears to be in perception of RP. However, there is lack of research to make more certain conclusions. Future researchers should also take into consideration gender, sport experience, age, taking responsibility, self-confidence, attributions, expectations, superstitions, emotions, perception of achievement etc.